Lessons from the Mexican environmental experience : first results from NAFTA - Schatan, C. (IDRC, Ottawa, ON, CA, 2000)
In IDL-34998 Mexico is the only developing country that has entered a free trade agreement that incorporates an environmental clause. The North Atlantic Free Trade Agreement (NAFTA) was controversial in terms of its ecological impact. The Environmental Side-Agreement (ESA) was one of the most sensitive issues in NAFTA negotiations. This chapter discusses the institutional framework of the agreement, and whether NAFTA and other agreements signed with the United States will help Mexico to improve environmental conditions. An important aspect of the agreements on the environment, and recognized by all three parties is that they take precedence over national rules. Initiatives for tri-lateral cooperation on environmental issues are examined